2020
DOI: 10.1186/s12879-020-05066-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology and socio-demographic risk factors of sexually transmitted infections among women in Lebanon

Abstract: Background Sexually transmitted infections (STIs) cause a major public health problem that affect both men and women in developing and developed countries. The aim of the study was to estimate the prevalence of 11 STIs among women who voluntarily participated in the study, while seeking gynecological checkup. The existence of an association between the presence of pathogens and symptoms and various sociodemographic risk factors was assessed. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 48 publications
4
12
2
Order By: Relevance
“…The original research article conducted in Korea reported prevalence of 16.7% with the high risk HPV type of 12.5% [58] which is too far up when compared with the pooled estimates of the current review which focused on HIV positive women. In addition, the study among Arab women indicated 6.2% among Qatari women and 5.9% non-Qatari women [59] somewhat concordant with the study conducted in Lebanon which reported HPV prevalence of 6.7% [60]. This variation is probably attributed to the differences in the study settings, sample sizes used and the studied population.…”
Section: Discussionsupporting
confidence: 81%
“…The original research article conducted in Korea reported prevalence of 16.7% with the high risk HPV type of 12.5% [58] which is too far up when compared with the pooled estimates of the current review which focused on HIV positive women. In addition, the study among Arab women indicated 6.2% among Qatari women and 5.9% non-Qatari women [59] somewhat concordant with the study conducted in Lebanon which reported HPV prevalence of 6.7% [60]. This variation is probably attributed to the differences in the study settings, sample sizes used and the studied population.…”
Section: Discussionsupporting
confidence: 81%
“…Rates of HIV, Hepatitis and Syphilis were low; however, symptoms associated with a bacterial/parasitic STI (Neisseria Gonorrhea and/or Chlamydia Trachomatis, Ureaplasma Urealyticum/Parvum, Mycoplasma Genitalium, and Trichomonaisis) were relatively high among the subset that underwent medical consultations. In fact, symptoms indicative of gonorrhea/chlamydia were higher than the prevalence reported in a local study on a sample of 505 women 14 . It is important to note that the reported rates are most likely underreported since these infections can often be asymptomatic.…”
Section: Discussioncontrasting
confidence: 64%
“…The prevalence of genital warts of 15% was also higher than the rate reported in the local study 14 . Even though this study reported prevalence of HPV based on the presence of genital warts (caused by non-cancerous strains of HPV) evidence attests to an increased risk of HPV-related cancer among those who have had genital warts 15 , 16 .…”
Section: Discussioncontrasting
confidence: 62%
“…27 Most studies have reported that the rate of having multiple infections is much more common in younger women aged 16–19 years than in those aged above 35 years. 66 , 67 A study conducted in South Africa amongst pregnant women living with HIV reported the rate of coinfections to be 2.6% for C. trachomatis and N. gonorrhoeae , 8.6% for C. trachomatis and T. vaginalis , 0.7% for N. gonorrhoeae and T. vaginalis , and 1.4% had all three STIs. 22 Another study by Joseph et al 18 reported that in pregnant women living with HIV, 50% of those were coinfected when compared with 16% of women living without HIV who were coinfected ( p < 0.01).…”
Section: Introductionmentioning
confidence: 99%
“…Sexually transmitted infections have been reported to be associated with pelvic inflammatory disease (PID), adverse pregnancy outcomes, cervical cancer, infertility and multiple reproductive tract sequelae. 29 , 38 , 40 , 44 , 66 , 67 , 94 , 95 During pregnancy, untreated STIs may lead to a variety of complications including intrauterine death (spontaneous abortion), preterm delivery, intrauterine growth restriction, ectopic pregnancy, postpartum sepsis, congenital infection, stillbirth and low birth weight, miscarriage, neonatal conjunctivitis, neonatal pneumonia, premature rupture of membranes and chorioamnionitis. In men, subsequent subfertility may arise.…”
Section: Introductionmentioning
confidence: 99%